DETEKSI DINI DAN EDUKASI FAKTOR RISIKO HIPERTENSI PADA REMAJA DI KOTA TOMOHON - Malonda, Nancy S H; Kawatu, Paul A T; Sanggelorang, Yulianty (Jurnal Ilmiah Tatengkorang, 2025)
Background: Hypertension, or high blood pressure, has been recognized as a major global health issue. While it is often linked to older age, the prevalence of hypertension among adolescents has been on the rise. Hypertension in adolescents is particularly concerning because it can persist into adulthood, increasing the risk of morbidity and mortality. Although clinical prevalence among children and adolescents is lower than in adults, research suggests that essential hypertension in adults often begins during adolescence. Therefore, it is essential to empower the community to manage its risk factors effectively.Objective: This program aims to enhance public knowledge, particularly among adolescents, on how to control the risk factors for hypertension. The goal is to equip adolescents with accurate knowledge of hypertension risk factors.Methods: The methods employed in this program include health education through counseling sessions and blood pressure measurements conducted among adolescents, specifically students from SMA Katolik Karitas Tomohon and SMP Katolik Gonzaga Tomohon.Results: Statistical analysis using the T-test revealed a significant difference in students' knowledge before and after the counseling sessions, with a p-value of 0.000. This indicates a significant increase in adolescents' knowledge about hypertension after receiving counseling. Early detection through blood pressure measurements showed an increase in blood pressure among some adolescents. The majority of students, 56 (71.8%), had normal blood pressure, while 12 students (15.4%) exhibited elevated blood pressure. Furthermore, 6 students (7.7%) were classified as having stage 1 hypertension, and 4 students (5.1%) were found to have stage 2 hypertension.